Factors affecting professional identity formation of basic medical sciences teachers in Pakistan: a phenomenological analysis of interviews - Kiran, Faiza; Javaid, Arshad; Irum, Shazia; Zahoor, Asiya; Farooq, Fareeha (Frontiers in Education, 2024)
Teachers can think, feel, and act like a teacher only if they have a strong professional identity.The purpose of our study was to identify factors shaping the unique professional identity of basic medical sciences teachers in our context. A qualitative study is performed using phenomenology.Purposive sampling was obtained. Iterative data collection and analysis was done till data saturation, by sending Google form link of a 20 item-text based interview to Basic Medical Sciences Teachers. A total of 40 participants took part in the study. Nine categories were identified and grouped into two major themes: four personal and five environmental factors.Personal factors include characteristics, preferences, religious values, and professional development whereas environmental factors include Community of Practice, students' feedback, administrative support, work environment and societal apathy. Of these, aptitude, family preference/work life balance, hard work, dedication and effect on parenting were factors more evident in females, whereas passion, experience, complacency, and unique identity were prominent in males. Community of practice 31(77%) , passion for teaching 21(52%), students' feedback 18(45%), work-life balance 16(40%) and religious values 13(32%) all are prime positive contributors to the identity of basic medical sciences teachers whereas poor administrative support 8(20%), negative work environment 11(27%), job dissatisfaction 7(17%), societal apathy 4(10%), lack of opportunities for professional growth 6(15%), negatively impact professional identity of basic medical sciences teachers.